The Study Of Effects Of Dealing With Paper Monetary And Change To Electronic Cards On The Syrian Economy - اسماعيل, عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research deals with an analytical study of the reflections of cancellation of the paper monetary and applying the electronic payments on the Syrian Economy. Initially, the research aims to throw a light on the reality of the Syrian economy, touching on the most important difficulties that currently facing. Then, studying the reasons that lead to cancellation paper Cash and transferring to the electronic payment such as the increase of the tax and Custom evasion and merchant's monopoly of some commodities in crisis , price manipulating , the difficulty of implementing some governmental decisions and the great distortion in the distribution of government support. The research also aims to try to present an appropriate mechanism for the application of the electronic payment that suits the reality of the Syrian Economy. With all its components and entities with presenting some practical applications on the study Finally, the research provides a set of economic implications to cancellation Paper Cash and application the Electronic payment in terms limitation tax and customs evasion directing government support policies and controlling markets. The research adopted the descriptive -analytical approach focusing on the official governmental reports of the figures that were adopted in the analysis. The study reached to a set of results the most prominent of which is related to increase of tax evasion in Syria by 88% and the same of the custom evasion in addition to the difficulty of implementing any special governmental economic policies regarding the re - distribution of the support to the poorest groups due to the fact that the economic and financial cycles is completely beyond the scope of government supervision.